Truth and relevancy - Romero, Gustavo Esteban (2017)
There are several types of truths. In this paper I focus on semantic truths, and within these on factual truths. These truths are attributed to statements. I review the theory of the truth proposed by Bunge and discuss some problems that it presents. I suggest that a theory of truth of factual statements should be complemented by a theory of relevance, and propose the basic tenets of it. Finally, I briefly discuss the nature of propositions and the problem of scientific truth in the light of the presented semantic theory.